Correlation between Perceptions of School Support and The Mastery Of Information Technology to Teachers' Self-Efficacy - Missa Serriawati; Saifuddin Azwar (Journal of Psychology and Instruction, 2020)
Curriculum 2013 requires teachers to master information technology in order to teach in a better way. In fact, many elementary school teachers have not been able to use computers. Lack of school support and information technology skills may be associated with low self-efficacy. The purpose of this study is to determine whether teachers’ self-efficacy can be predicted by school support and mastery of information technology. Subjects of this research were 225 teachers from 19 elementary schools in Daerah Istimewa Yogyakarta province, which have become the pilot project of Curriculum 2013. Instruments used in this study were Self Efficacy Scale, School Support Scale, and Information Technology Test. The data were analyzed using multiple linear regression analysis. The result of this study found that school support and mastery of information mastery simultaneously positively correlated to teachers’ self-efficacy with a correlation value of 139,616    significance level p<0,01. The effective contribution of school support and mastery of information mastery together positively correlated to teachers’ self-efficacy is 55,7%.